1991
DOI: 10.1038/349117a0
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase superfamily: conserved structure and molecular mechanism

Abstract: GTPases are conserved molecular switches, built according to a common structural design. Rapidly accruing knowledge of individual GTPases--crystal structures, biochemical properties, or results of molecular genetic experiments--support and generate hypotheses relating structure to function in other members of the diverse family of GTPases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
2,392
1
34

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 3,259 publications
(2,466 citation statements)
references
References 147 publications
39
2,392
1
34
Order By: Relevance
“…Bms1p, a G-domain protein associates with Rcl1peach case, affinity purification of the complex, followed by mass spectrometry, identified the expected protein partner, either Bms1p or Rcl1p+ In addition, variable levels of several ribosomal proteins copurified+ We are investigating whether they originate from the contaminating preribosomal particles or represent components of the 10S complex (D+ Hess, E+ Billy, T+ Wegierski, & W+ Filipowicz, unpubl+ results)+ Rcl1p-like proteins are conserved among eukaryotes and the mouse ortholog, mRcl1, complements growth of a yeast strain depleted of Rcl1p + Likewise, proteins similar to Bms1p are expressed in other eukaryotes, and we have isolated a human Bms1p homolog while carrying out a two-hybrid screen using human Rcl1 as bait (our unpubl+ results)+ Thus, the interaction between the two proteins seems to be evolutionarily conserved+ An intriguing finding of this work is that Bms1p, a protein required for pre-rRNA processing, contains an evolutionarily conserved region resembling the guanine nucleotide binding domain, or "G domain," found in many regulatory GTPases (Bourne et al+, 1991;Sprang, 1997;Sprinzl et al+, 2000)+ The presence in YPL217Cp/Bms1p of a domain with strong structural similarity to the G domain of the bacterial elongation factor EF-Tu has been noted previously by Sanchez and Sali (1998), who carried out a genome-wide modeling of yeast proteins+ We have found that amino acid mutations in the two motifs involved in GTP/GDP and/or Mg 2ϩ binding in known G proteins, inactivate Bms1p+ Moreover, Gelperin and Lemmon (pers+ comm+) have demonstrated specific crosslinking of GTP to the overexpressed protein+ These data indicate that Bms1p is a true member of the G protein superfamily+ Members of this family include regulatory GTPases involved in many different cellular processes, ranging from ribosomal protein synthesis (e+g+, translation factors IF-2, EF-Tu, and EF-G), through signal transduction and membrane signaling (e+g+, ras, and heterotrimeric G proteins), to protein traffic and cytoskeleton organization (e+g+, Ran and Rho proteins)+ Common to the functioning of these proteins is that their G domains generally act as molecular switches, which are active in the GTP-bound form and inactive in the GDP-bound form+ GTP hydrolysis and exchange of GDP for GTP to reactivate the protein are usually assisted by other regulatory factors (Bourne et al+, 1991;Sprang, 1997;Sprinzl et al+, 2000)+ Hydrolysis of GTP bound to Bms1p might act as a signal to initiate pre-rRNA cleavage reactions following the correct assembly of the processing complex+ In this context, the proposed interaction of Bms1p and Rcl1p with U3 snoRNP at the level of nascent ribosomes is particularly intriguing and makes Bms1p, either alone or in association with Rcl1p, very well suited to perform such a regulatory role+ Much evidence exists that U3 is a key snoRNP required for 18S rRNA processing and 40S biogenesis (see the Introduction)+ Among several proteins that are specifically associated with U3 snoRNP and required for A 0 -A 2 or A 1 -A 2 processing (see the Introduction), are Sof1p and Dhr1p+ Sof1p contains a repeated sequence found in the b subunit of the heterotrimeric G proteins and some other regulatory proteins (Jansen et al+, 1993), whereas Dhr1p is a member of the DEAH subfamily of putative ATP-dependent RNA helicases; Dhr1p was shown to efficiently coprecipitate with …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Bms1p, a G-domain protein associates with Rcl1peach case, affinity purification of the complex, followed by mass spectrometry, identified the expected protein partner, either Bms1p or Rcl1p+ In addition, variable levels of several ribosomal proteins copurified+ We are investigating whether they originate from the contaminating preribosomal particles or represent components of the 10S complex (D+ Hess, E+ Billy, T+ Wegierski, & W+ Filipowicz, unpubl+ results)+ Rcl1p-like proteins are conserved among eukaryotes and the mouse ortholog, mRcl1, complements growth of a yeast strain depleted of Rcl1p + Likewise, proteins similar to Bms1p are expressed in other eukaryotes, and we have isolated a human Bms1p homolog while carrying out a two-hybrid screen using human Rcl1 as bait (our unpubl+ results)+ Thus, the interaction between the two proteins seems to be evolutionarily conserved+ An intriguing finding of this work is that Bms1p, a protein required for pre-rRNA processing, contains an evolutionarily conserved region resembling the guanine nucleotide binding domain, or "G domain," found in many regulatory GTPases (Bourne et al+, 1991;Sprang, 1997;Sprinzl et al+, 2000)+ The presence in YPL217Cp/Bms1p of a domain with strong structural similarity to the G domain of the bacterial elongation factor EF-Tu has been noted previously by Sanchez and Sali (1998), who carried out a genome-wide modeling of yeast proteins+ We have found that amino acid mutations in the two motifs involved in GTP/GDP and/or Mg 2ϩ binding in known G proteins, inactivate Bms1p+ Moreover, Gelperin and Lemmon (pers+ comm+) have demonstrated specific crosslinking of GTP to the overexpressed protein+ These data indicate that Bms1p is a true member of the G protein superfamily+ Members of this family include regulatory GTPases involved in many different cellular processes, ranging from ribosomal protein synthesis (e+g+, translation factors IF-2, EF-Tu, and EF-G), through signal transduction and membrane signaling (e+g+, ras, and heterotrimeric G proteins), to protein traffic and cytoskeleton organization (e+g+, Ran and Rho proteins)+ Common to the functioning of these proteins is that their G domains generally act as molecular switches, which are active in the GTP-bound form and inactive in the GDP-bound form+ GTP hydrolysis and exchange of GDP for GTP to reactivate the protein are usually assisted by other regulatory factors (Bourne et al+, 1991;Sprang, 1997;Sprinzl et al+, 2000)+ Hydrolysis of GTP bound to Bms1p might act as a signal to initiate pre-rRNA cleavage reactions following the correct assembly of the processing complex+ In this context, the proposed interaction of Bms1p and Rcl1p with U3 snoRNP at the level of nascent ribosomes is particularly intriguing and makes Bms1p, either alone or in association with Rcl1p, very well suited to perform such a regulatory role+ Much evidence exists that U3 is a key snoRNP required for 18S rRNA processing and 40S biogenesis (see the Introduction)+ Among several proteins that are specifically associated with U3 snoRNP and required for A 0 -A 2 or A 1 -A 2 processing (see the Introduction), are Sof1p and Dhr1p+ Sof1p contains a repeated sequence found in the b subunit of the heterotrimeric G proteins and some other regulatory proteins (Jansen et al+, 1993), whereas Dhr1p is a member of the DEAH subfamily of putative ATP-dependent RNA helicases; Dhr1p was shown to efficiently coprecipitate with …”
Section: Discussionmentioning
confidence: 82%
“…Coprecipitation of Bms1p and Rcl1p, and domain organization of Bms1p+ A: Bms1p-ProtA immunoprecipitates Rcl1p+ Inputs, supernatants, and pellets (loaded in a 1:1:10 ratio) from the IP reactions of ProtA-tagged proteins expressed in the strains indicated were analyzed by western blotting using a-Rcl1p Ab+ The efficiency of Rcl1p coimmunoprecipitation was estimated as 20%+ Incomplete recovery of Rcl1p may be explained by a low efficiency of Bms1-ProtA immunoprecipitation (about 50%; not shown), susceptibility of Bms1p to degradation (see Fig+ 2C), and the fact that a substantial fraction of Rcl1p exists as a free form ; this work)+ B: Domain organization of Bms1p and a comparison with the structurally related yeast protein, YDL060Wp+ Percentages of sequence identity and similarity (in parentheses) between the N and C domains of Bms1p (in regions of similarity shown by down-sloping hatch), and between the two proteins (in regions of similarity shown by up-sloping hatch) are indicated+ The black bar designates the G-like domain, and the black vertical lines the predicted nuclear localization signals+ C: Alignment of the G-like domains of BMS1 proteins from S. cerevisiae (BMS1 Sc) and H. sapiens (BMS1 Hs) with the G domains of selected translation factors of different origin: elongation factors EF-Tu from E. coli (EFTu Ec; accession number CAA40370) and EF1-alpha from S. cerevisiae (EF1a Sc;CAA25798), and the initiation factor IF2 from Bacillus subtilis (IF2 Bs; CAB13536) and yeast mitochondria (mIF2 Sc; NP_014619)+ The five G motifs are indicated, with the most conserved residues marked with asterisks+ The alignment was done manually and is based on available alignments of translation initiation and elongation factors, and also on results of the Blast searches carried out with BMS1 proteins+ 1256 T. Wegierski et al Bourne et al+, 1991;Sprang, 1997; see also the Discussion)+ Sequences of the G-like domains of BMS1 proteins are most closely related to the G domains of the eubacterial protein synthesis initiation and elongation factors IF2 and EF-Tu (Fig+ 1C; data not shown)+ Indeed, the presence in YPL217Cp/Bms1p of a domain with strong three-dimensional structural similarity to the G domain of EF-Tu has been noted previously by Sanchez and Sali (1998), who carried out a genome-wide modeling of yeast proteins+ G domains of nearly all regulatory GTPases have five conserved polypeptide loops designated G1 through G5, which form contact sites with the guanine nucleotide or coordinate the Mg 2ϩ ion (Bourne et al+, 1991;Kjeldgaard et al+, 1996;Sprang, 1997;Song et al+, 1999;Roll-Mecak et al+, 2000;Sprinzl et al+, 2000, and references therein)+ Sequences resembling G1 (consensus [G,A]X 4 GK [S,T]; also known as a P-loop), G4 (consensus [N,T]KXD), and G5 (consensus for translation factors S [A,G]) are present in all BMS1 proteins, and either fully conform with the consensus or contain, at most, single conservative substitutions (Fig+ 1C)+ The G2 motif (consensus for translation factors, GIT) is...…”
Section: Identification Of Bms1p As a Protein Interacting With Rcl1pmentioning
confidence: 99%
“…Transfected cells were cultured and assayed by R-SAT TM as described in the Materials and methods. Rac*, ras* and Ga13* are constitutively activated by mutations (to rac Q61L, ras G12V and Ga13 Q226L respectively) which impair their intrinsic GTPase activities (see Bourne et al, 1991). Fold stimulation was calculated as the ratio of G-protein response to control response.…”
Section: Resultsmentioning
confidence: 99%
“…DNA was transfected into 2610 5 cells per well of a six-well plate. rac Q61L, ras G12V and Ga13 Q226L are constitutively activated by mutations which impair GTPase activity (see Bourne et al, 1991) and are referred to as rac*, ras* and Ga13*. rac T17N and ras T17N are dominant negative alleles each containing a mutation which abolishes GTPbinding but preserves GDP-binding (Feig and Cooper, 1988) and are referred to as rac (7) and ras(7).…”
Section: Functional Assaysmentioning
confidence: 99%
See 1 more Smart Citation